ANALISIS KERUSAKAN MESIN AHU MENGGUNAKAN PENDEKATAN METODE FAILURE MODE AND EFFECT ANALYSIS - Muhamad Ikhsan Ramadhan; Jojo Sumarjo; Farradina Choria Suci; Deri Teguh Santoso (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2021)
The manufacturing industry is currently experiencing rapid development from various aspects. This aspect develops, it is increasingly necessary to find solutions to get more effective and efficient results. The Air Handling Unit (AHU) machine is a heat exchanger between cold water and air. The method used to identify the damage is the Failure Mode and Effect Analysis (FMEA) method. With this method, it is hoped that the point of damage that occurs can be known and can be planned for further maintenance. The results of the analysis of the FMEA method were obtained from related fields regarding the damage to the AHU engine components. Based on the results of the analysis of the Pareto diagram, it can be seen that there are several types of damage that dominant in the Air Handling Unit engine, namely; Motors & blowers; Pipe; Air Filter; Spray Nozzles. According to the principle of the Pareto diagram, which is 80/20, it means that 80% of damage to the machine is caused by 20% of the causes of damage. In this case damage the motor & blower, pipelines, air filters must be prioritized for maintenance so that the quality and efficiency of the engine is getting better.